Assessment of Anxiety in Cognitive-Behavior Therapy in Young University Students with Autism Spectrum Disorders: A Review - Sarah Sánchez-Cueva; Yurena Alonso-Esteban; Francisco Alcantud-Marín (MDPI AG, 2021)
The university provides academic support to disabled students, however, few institutions provide academic, extra-academic or preventive support to students with Autism Spectrum Disorders High-Functioning (ASD-HF). Among the most commonly requested needs is support for coping with anxiety arising from academic and social activity itself. When planning an intervention program, it is necessary to screen those who have problems and are likely to benefit from such a program. In this article we propose a systematic search for measures of anxiety for young people and adults with ASD-HF. Of a total of 683 documents, only 7 met the selection criteria. Of these, a total of 35 tools were detected, of which only 11 mediated anxiety. Screening should be carried out for all students, so that we can detect the "risk" of anxiety disturbance in all cases and, in particular, in students with ASD-HF. However, the instruments eligible for assessing intervention outcomes should be agreed upon in order to be able to compare results from different trials.